See56.7 cause it is the correct one to the 20th
Answer:
The option A,D and E are correct.
Step-by-step explanation:
Given: 2x^3-250x^2
Factor : 2x^2(x-125)
So, GCF = 2x^2
Now a = 1 and b= 5
we know that a^3-b^3 = (a-b)(a^2+ab+b^2)
(x)^3 - (5)^3 = (x-5)(x^2+5x+25)
So, the option A,D and E are correct.
Answer:
c
Step-by-step explanation:
The graph is gradually decreasing but stops
Answer:
f(x) = -x³ + 3x² + 4x - 12
Step-by-step explanation:
f(x)=(x+2)(-x+3)(x-2)
Step 1. Use the difference of two squares
(x + 2)(x - 2) = x² - 4
f(x) = (-x + 3)(x² - 4)
Step 2. Long multiplication
x² - 4
<u>-x + 3 </u>
-x³ + 4x
<u> + 3x² - 12</u>
-x³ + 3x² + 4x - 12
f(x) = -x³ + 3x² + 4x - 12